Management of permanent change - Albach, Horst; Meffert, Heribert; Pinkwart, Andreas; Reichwald, Ralf (Springer Fachmedien Wiesbaden Imprint: Springer Gabler, 2015)
In the current times of more frequent crises and ever shortening innovation cycles, the management of change has become a crucial task of survival. While it is not a new topic in business research, the developments of the last decade have posed many new challenges for the change management of firms and organizations, and have thus also raised many new questions for academic research in business administration, which the present book turns to deepen. Its particular focus is on disruptive change including its driving forces as well as effective and sustainable management. This publication constitutes a collection of articles that discuss change and innovation processes across different sectors of the economy (industry, banking, and retail), the role of leadership and corporate governance for the effectiveness and sustainability of organizational change.   The editors Prof. Dr. Dr. h.c. mult. Horst Albach, Professor Emeritus, Humboldt-Universität zu Berlin. Prof. Dr. Dr. h.c. mult. Heribert Meffert, Professor Emeritus, University of Münster. Prof. Dr. Andreas Pinkwart, Dean of HHL Leipzig Graduate School of Management. Prof. Dr. Prof. h.c. Dr. h.c. Ralf Reichwald, Professor Emeritus of Excellence, Technische Universität München. The editors are the founders and academic directors of the Center for Advanced Studies in Management (CASiM), an interdisciplinary research center of HHL Leipzig Graduate School of Management devoted to key research topics of business administration for the 21st century.